METODE VAKT TERHADAP KEMAMPUAN MEMBACA ANAK KESULITAN BELAJAR DI SDN - Sugiharto, Hendy (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   Reading was one of the aspects of speech skill which should be mastered by either general students or special need children, included difficulty learning children. Difficulty learning students were those who had disorder in learning process influenced by either internal or external factors. For learning difficulty children, mastering reading ability was not easy thing because they had disorder in understanding process or integrating the components of alphabets, words, and sentences. It required a method which could stimulate the learning modality. The Visual, Auditory, Kinesthetic, Tactile (VAKT) method was used by interactive video media and counterfeit alphabets. This research had purpose to analyze whether there was influence of VAKT method toward reading ability to learning difficulty children in SDN Masangan Kulon Sukodono Sidoarjo. The research kind used was pre-experiment. The design used: one group pre test and post test. The method used to collect the data was test and documentation. For data analysis, the research used analysis technique of statistic non parametric with wilcoxon match pair test. The result after using VAKT method indicated that Zh = 2,20 > Zt = 1,96 it indicated that “there was significant influence of VAKT method toward reading ability to learning difficulty children”.   Keywords: Reading ability, VAKT method